Impact of Preoperative Medical Comorbidities on Anesthetic Risk and Surgical Outcomes in Patients with Long Bone Fractures: A Clinical Study - Faisal Toheed, Salman Habib Abbasi, Mobasher Ahmad Saeed, Muhammad Yousuf Memon, Khan Muhammad Yaqub, Saifullah (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Long bone fractures are a common cause of orthopedic trauma requiring surgical fixation. Preoperative medical comorbidities are known to influence anesthetic risk and postoperative recovery; however, their independent impact in trauma patients remains underexplored. Objective: To evaluate the effect of preoperative medical comorbidities on anesthetic instability and early surgical outcomes in patients undergoing operative fixation of long bone fractures. Methods: This prospective clinical study was conducted at Pakistan Ordnance Factories (POF) Hospital, Wah Cantt, Pakistan, from January 2022 to June 2023. A total of 100 patients with long bone fractures requiring surgical fixation were included. Data on demographics, fracture characteristics, comorbidities, ASA classification, anesthesia details, intraoperative hemodynamic stability, and postoperative outcomes were collected. Primary outcomes included intraoperative anesthetic instability and 30-day postoperative complications such as surgical site infection, pulmonary complications, acute kidney injury, major adverse cardiac events, venous thromboembolism, reoperation, and mortality. Statistical analysis was performed using SPSS version 26, with logistic regression applied to identify independent predictors. Results: The mean age of patients was 52.6 ± 16.8 years, with males accounting for 62% of the study population. Common comorbidities included hypertension (42%), diabetes mellitus (30%), anemia (28%), ischemic heart disease (15%), and chronic kidney disease (10%). Intraoperative anesthetic instability occurred in 27% of patients, significantly more frequent among ASA III–IV patients (p=0.003). Overall postoperative complication rate was 26%, with surgical site infection (9%), pulmonary complications (8%), acute kidney injury (5%), and major cardiac events (4%) being most common. Diabetes was associated with higher infection risk (p=0.02), chronic kidney disease with postoperative AKI (p=0.004), and ischemic heart disease with cardiac events (p=0.01). Patients with complications had significantly longer hospital stays compared to those without complications (10.2 vs. 6.1 days, p<0.001). Conclusion: Preoperative comorbidities, particularly diabetes mellitus, ischemic heart disease, chronic kidney disease, COPD, and anemia, significantly increase anesthetic risk and postoperative complications in patients with long bone fractures. Higher ASA classification strongly predicts adverse outcomes. Comprehensive preoperative optimization and avoidance of unnecessary surgical delays are critical to improving outcomes in orthopedic trauma patients. Keywords: long bone fractures, comorbidities, anesthetic risk, surgical outcomes, ASA classification, orthopedic trauma